PENGARUH ZAKAT DAN INDEKS PEMBAN PENGARUH ZAKAT DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN - Mirza irwanda (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2021)
Abstract This research is motivated because poverty is one of the economic problems experienced in every country including Indonesia, Indonesia as one of the largest Muslim countries actually has one solution in alleviating poverty, namely zakat. Zakat if managed optimally is expected to be able to eliminate the gap between people who have excess assets and people who still need one of the indicators by increasing the Human Development Index (HDI) which in turn can have an effect on efforts to reduce poverty levels. The research method used is the Anylisis data panel where samples were taken as many as 12 provinces in Indonesia for 7 years starting from 2012 to 2017. The results of the study show that zakat has an effect on reducing the level of poverty in Indonesia. Keywords: Zakat, Human Development Index, Poverty